(untitled) (Nigerian Journal of Health Sciences, 2023)
Glossopalatal and congenital alveolar synechiae are rare and often occur in association with orofacial anomalies. The occurrence of sub‑glossopalatal membrane causing restrictive mouth opening associated with complete cleft of hard palate has not been reported from Africa. A report of a case of the subglossopalaal membrane and its management in a term male child delivered per vaginum by a 24‑year‑old primiparous woman in a rural setting in Nigeria. All available English literature was search using Medline, PubMed, and Google scholar. A 3‑day‑old boy was presented because of a restrictive mouth opening due to sub‑glossopalatal membrane associated with a palatal cleft that made him to choke when feeding and snores all the time. He was admitted and nursed prone to allow the tongue to fall forward and prevent airway obstruction. He was also fed through nasogastric tube. He had a successful excision of membrane under local anesthesia on the 10th day of life. He did well postexcision and was placed on cup and spoon feeding while awaiting a palatal cleft repair. He had an uneventful cleft palate repair at 10 months of age. This is the first African report of sub‑glossopalatal membrane associated with a cleft palate. A careful management brings good outcome.